2017
DOI: 10.1177/0021998316688950
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of delamination and kerf geometry of carbon epoxy composite machined by abrasive water jet

Abstract: The present article focuses on mechanism of delamination and kerf geometry in abrasive water jet machining of carbon epoxy composite. In the present study, four process parameters of abrasive water jet machining namely hydraulic pressure, traverse rate, stand-off distance, and abrasive mass flow rate are considered. The experiments are performed on the basis of response surface methodology as a statistical design of experiment approach. Delamination in machined samples is observed by using scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 29 publications
8
63
1
1
Order By: Relevance
“…In this study, the minimum conicity that can be obtained was indicated by applying high hydraulic pressure combined with a small stand-off distance. The conicity obtained is reduced by increasing the feed rate, contrary to the findings of Dhanawade et al [27]. This is because, at high pressures, an increase in feed rate generates a smaller upper width (Wt), producing a more constant cut.…”
Section: Introductioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In this study, the minimum conicity that can be obtained was indicated by applying high hydraulic pressure combined with a small stand-off distance. The conicity obtained is reduced by increasing the feed rate, contrary to the findings of Dhanawade et al [27]. This is because, at high pressures, an increase in feed rate generates a smaller upper width (Wt), producing a more constant cut.…”
Section: Introductioncontrasting
confidence: 71%
“…Dhanawade et al [27] carried out a study on abrasive waterjet cutting in a thermoset polymeric matrix composite material. The CFRP used was 26 mm thick.…”
Section: Introductionmentioning
confidence: 99%
“…Pratik Bose et al [9] get impact of water pressure and abrasive flow rate on surface roughness for GFRP composites. Ajit Dhanawade et al [10] used stand-off distance, jet pressure, traverse speed, and abrasive mass flow rate as a performance parameters and delamination and kerf geometry as performance parameter while experimenting on carbon epoxy composites. The result shows that delamination mainly depends on water pressure, abrasive flow rate and transverse speed whereas kerf taper ratio depends on transverse rate and SOD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abrasive water jet machining is now presently used in various metal cutting process. The Abrasive Water Jet (AWJ) machining parameters such as jet operating water pressure (WP), transverse speed (TS), Standoff Distance (SOD), and concentration of abrasive are important for controlled cutting operation [1]. The quality of machining can be improved by controlling the AWJM parameters [2].…”
Section: Introductionmentioning
confidence: 99%